Quantification Of Glycosaminoglycans In Knee Synovial Fluid From Different Patient Groups And Knee-Healthy Subjects Using High Performance Liquid Chromatography - Andersson, E.; Tykesson, E.; Struglics, A. (Osteoarthritis and cartilage, 2023)
Purpose: The glycosaminoglycans chondroitin sulfate (CS) and hyaluronic acid (HA) are important for the normal function of articular cartilage, and changes of their sulfation and concentration may play a role in the pathogenesis of osteoarthritis (OA). Therefore, these glycans may be clinically useful as biomarkers in OA management. The purpose of this study was to analyze the CS and HA pattern in knee synovial fluid from different subject groups.Methods: OA patients (n=20, age=34-75 years, 45% women), recently knee-injured patients (0-77 days from injury, n=46, age 15-64 years, 15% women), previously knee-injured patients (88 days-21 years from injury, n=30, age 25-65 years, 17% women) and knee-healthy subjects (n=22, age 17-48 years, 23% women) were selected from a cross-sectional convenience cohort. CS and HA in individual synovial fluid samples, a synovial fluid quality control sample (SF-QC; a pool of synovial fluids) and a CS quality control sample (CS-QC) were digested with chondroitinase ABC and glucose oxidase overnight. Samples and glycan standards (CS [n=6] and HA [n=1] standards) were labelled with 2-aminoacridone (AMAC) and analyzed using a quantitative high performance liquid chromatography (HPLC) assay. In total, 118 synovial fluid samples were run, whereof 34 in duplicates. SF-QC, CS-QC and standards were run in duplicates.Since the CS and HA data were not normally distributed, non-parametric analyses for group comparisons were done (Student’s T-test for age analysis, Chi-square test for sex analysis and Mann-Whitney U test for CS and HA analysis). The significance level was set at pResults: HPLC assay validation: The intra experiment coefficient of variation (CV) for the synovial fluid samples (n=36; including SF-QC) was 0.03-36.9% (median 5.4%) for CS and 0.4-44.9% (median 7.6%) for HA; intra CV for the CS-QC sample was 0.01-3.7%, and for the standards it was 0.2-6.7% for CS and 1.9-7.1% for HA. The inter experiment CV for SF-QC (n=5 experiments) was 9.8-17.5% for CS and 15.1% for HA; the inter CV for CS-QC (n=4 experiments) was 3.4-6.1%, and for the standards (n=5 experiments) it was 0.01-0.07% for CS and 0.1% for HA. Glucose oxidase was added to remove glucose that otherwise co-elutes with non-sulfated CS; it did not affect the CS and HA standards (data not shown). Group comparisons: Comparisons were made between the knee-healthy control group and the OA, recent injury and previous injury groups respectively, as well as between the recent injury and previous injury groups. There was no difference in sex between either of the groups (p=0.074-0.866). There was no difference in age between the knee-healthy group and the recent injury group (p=0.330), but the knee-healthy group was younger than the previous injury group and the OA group (pConclusions: Our data suggests that the groups with knee pathologies have higher concentrations of some CS variants and HA than the knee-healthy group. We also see a trend of higher levels of CS variants in the recent knee injury group compared to the previous knee injury group. This indicates that there is both an acute and chronic increase in the concentrations of CS variants and HA in synovial fluid following knee injury and/or cartilage damage.